THE EFFECT OF RETURN ON ASSETS, NET PROFIT MARGIN, AND DEBT TO EQUITY RATIO ON STOCK PRICES OF BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2019-2023 - Silvia Rizki Ramadana; Wardhiah; Rico Nur Ilham; Muttaqien (PT. Radja Intercontinental Publishing, 2025)
This study aims to analyze the influence of Return On Assets (ROA), Net Profit Margin (NPM), and Debt to Equity Ratio (DER) on stock prices of banking companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The research employs a quantitative approach using panel data regression. The sample was selected through purposive sampling and consists of 31 banking companies. Data was processed using EViews version 12 with the Random Effect Model (REM) approach, following a series of classical assumption tests. The results show that ROA and DER have no significant effect on stock prices, while NPM has a positive and significant effect. These findings indicate that net profit efficiency is a primary consideration for investors in evaluating the performance of banking companies in the capital market. The implications of this study can serve as input for bank management to strengthen profitability strategies in order to enhance company value in the eyes of investors.